Evaluation of the Implementation of Toddler Weighing Activities at the Integrated Service Post in the Sungai Pakning Public Health Center Work Area in 2021 - Apriani Dewi; Dedi Afandi; Lita Lita (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze evaluation of the implementation of toddler weighing activities at the Integrated Service Post in the Sungai Pakning Public Health Center Work Area in 2021. This study uses a qualitative type with a phenomenology research design. The main informants in this study were the Head of the Public Health Center, Nutrition Officer, 2 Implementing Midwives and the supporting informants were the Nutrition Program Holder of the Bengkalis District Health Office and Integrated Service Post cadres. The data analysis technique used in this qualitative research has several stages, including data reduction, data presentation, coding category, and conclusion drawing. The results show that evaluation of the implementation of toddler weighing activities at the Integrated Service Post in the Sungai Pakning Public Health Center Work Area in 2021 has not run properly. So, the suggestion for research is to create a training innovation for both Integrated Service Post cadres and officers involved in the implementation of toddler weighing activities at the Integrated Service Post in the form of hard skills training and soft skills training in the form of capacity building or emotional spiritual quotion training to build building learning commitment of Integrated Service Post cadres and health workers in providing services at the Integrated Service Post.